The Late Holocene tephra record of the central Mediterranean Sea: Mapping occurrences and new potential isochrons for the 4.4–2.0 ka time interval. (3rd November 2019) - Insinga, D. D.; Petrosino, P.; Alberico, I.; de Lange, G. J.; Lubritto, C.; Molisso, F.; Sacchi, M.; Sulpizio, R.; Wu, J.; Lirer, F.
ABSTRACT: Five cores from the southern Tyrrhenian and Ionian seas were studied for their tephra and cryptotephra content in the 4.4–2.0 ka time interval. The chronological framework for each core was obtained by accelerator mass spectrometry 14 C dating, the occurrence of distinct marker tephra and stratigraphic correlation with adjacent records. Tephrochronology allowed us to correlate the analyzed deposits with tephra markers associated with Somma‐Vesuvius (79 ad ), Ischia Island (Cretaio), Mt Etna (FG, FL and FS) and Campi Flegrei (Astroni‐Agnano Monte Spina) events. For the first time in the marine setting, a large single glass data set is provided for the Late Holocene Etnean marker beds including the FS tephra (ca. 4.3 ka). Moreover, unknown deposits from Lipari (ca. 2.2–2.0 ka) and Vulcano (3.6–3.3 ka) are also recognized at more distal sites than previously reported. These results contribute to improve the high‐resolution tephrostratigraphic framework of the central Mediterranean Sea. They also provide new insights into the chemical composition and dispersal pattern of tephras that can be used as inter‐archive tools for regional and 'local' stratigraphic correlations and for addressing paleoclimate research.